Attitudes towards offensive advertising: Malaysian Muslims' views - Butt, Mohsin; Fam, K.; Jong, H. (Emerald Group Publishing Limited, 2010)
Purpose – The purpose of this paper is to investigate the Malaysian Malays attitude towards offensive advertising and the reasons that make these advertisements offensive. This paper aims to explore the role of religiosity on attitudes towards controversial advertisements and the reasons why they are controversial. Design/methodology/approach – This paper consists of 279 randomly selected Malay participants. Data were analyzed using means, correlations, and ANOVA. Findings – Results indicate that those high on religiosity differ on the nature and manner of controversial advertisements from those of low religiosity. Malay Muslims when compared on their degree of religiosity differ in terms of their evaluation of offensive nature of advertisement. More important they differ more on the reason that make these advertisement offensive compared to the nature of the products. Research limitations/implications – Respondents are somewhat more skewed towards a younger population causing concern that the results might not be a true indication of all Malaysian age groups. Originality/value – The original value of the research lies in its effort to examine the results from the lens of religious theology and respondent degree of religiosity.